EMPOWERMENT STRATEGY JOINT BUSINESS GROUP (KUBE) ORCHID 6 IN INCREASE COMMUNITY WELFARE IN THE SUBDISTRICT SIANTAN HULU, NORTH PONTIANAK DISTRICT - Al Mujaddidah Hidayah Amsi; Zulkarnain (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to analyze the empowerment strategy applied by Anggrek 6 Joint Business Group (KUBE) in improving community welfare in Siantan Hulu Village, North Pontianak District. Using a descriptive qualitative approach, data was obtained through observation, in-depth interviews, and documentation of KUBE members, facilitators, and Social Service representatives. The results showed that effective empowerment strategies include participatory group formation, adaptive ongoing assistance, and activity planning based on local needs and potential. Drivers of success include support from community leaders and member motivation, while barriers include low education and geographical constraints. This study emphasizes the importance of a group-based empowerment approach in supporting the improvement of the socioeconomic welfare of poor urban communities.